The correlation between materialism, social comparison and status consumption among students - Pelser, T.; van Schalkwyk, P. J.; van Schalkwyk, J. H. (South African Journal of Higher Education, 2023)
South African students face many challenges when completing their tertiary education, finances being one of the most significant. This is not only due to a lack of monetary resources but also to students’ inability to manage their available resources. Students often make financial decisions not in their own interest due to both internal and external factors. Consequently, many students do not finish their studies or end up in debt. The research reported on in this article examined the correlation between three factors which influence spending and debt according to previous research, namely Materialism, Social Comparison and Status Consumption. These concepts refer to how much people value material possessions and how they compare their possessions to those of others and spend on status-conferring possessions to improve their image. This study used convenience sampling of 630 Generation Y students registered from four university campuses. Data collection was conducted using a self-reporting questionnaire. Data analysis comprised 597 valid questionnaires. The results reveal that Status Consumption can be predicted using Materialism and Social Comparison tendencies. The net result of this situation is that students first compare themselves to their peers and then spend money to feel better about themselves or present an improved image to their peers instead of investing their limited resources in their education. Very often, this spending is funded using credit. According to existing literature, this is true for students and the population at large and is one of the main drivers of the current debt problems South Africa is experiencing.